1027. Cerebrospinal Fluid Findings of Solid Organ Transplant Recipients with West Nile Virus Infections. (15th December 2022) - Abbas, Anum; Sikyta, Adia; Florescu, Diana F
Abstract: Background: In the solid organ transplant (SOT) population, West Nile virus (WNV) neuroinvasive disease can have significant morbidity and mortality. We evaluated cerebrospinal fluid (CSF) findings in neuroinvasive WNv infections among SOT recipients. Methods: We retrospectively reviewed medical records of all SOT recipients at our institution with WNv neuroinvasive disease (meningitis, encephalitis, meningo-encephalitis) from 2010 to 2018. Descriptive statistics were examined on key variables. Results: Eight transplant patients with mean age 54.47 years (12.79) were included: 5 kidney transplants, 1 in each kidney-pancreas, liver and lung transplants. Median time from transplant to infection was 49.8 months (2.7-175.4) and mean time-to-diagnosis 2 days (1.31) . On admission, mean total CSF WBC count was 134.57 cells/mm 3 (150.82), mean lymphocyte count 56.29 cells/mm 3 (32.32), mean neutrophil count 27.14 cells/mm 3 (34.34), and mean CSF protein 95.4 mg/dL (40.52mg/dL). West Nile virus CSF IgG at the time of diagnosis was negative in 7 patients, and not performed on 1 patient. WNv diagnosis is depicted below. Serum and CSF WNV Antibodies in Neuroinvasive Disease in SOT Recipients WNV CSF and serum IgG was negative at the time of diagnosis in 7/8 patients. Initial CSF IgM was positive in 3 out of 7 patients. Conclusion: WNv infection produces a CSF pleocytosis with neutrophilic predominance, though we noted more lymphocytic predominance among SOT recipients. CSF IgM and IgG are important diagnostics in neuroinvasive WNv. Disclosures: Diana F. Florescu, MD, AlloVir: Grant/Research Support|Merck: Advisor/Consultant|Merck: Grant/Research Support|NobelPharma: Grant/Research Support|Novavax: Grant/Research Support|Regeneron: Grant/Research Support|SymBio: Grant/Research Support|Takeda: Advisor/Consultant|Takeda: Grant/Research Support.